Smart Device Identification of Potsherds and Gemstones with Radiofrequency-Induced Harmonics Vibrations - Chen, Baxton R. (New Ideas Concerning Science and Technology Vol. 11, 2021)
Radiofrequencies can induce unique vibrational signatures in material such as potsherds and precious or semiprecious gemstones. We previously reported a method of identifying pottery shards based on their vibrational characteristics with ultrasound stimulation. We now detail the experimental procedure necessary for the extraction of such signatures from both ceramic shards and precious gems using radiofrequency stimulation. With both rapid and inexpensive vibrational signature extraction and comparison to a known database library, the technique provides a potential method of on-site material identification.